Pengaruh Profitabilitas , Dividend Terhadap Capital Structure Dengan Intelectual Capital Sebagai Variabel Intervening - Ana Sakinatun Nisa; Bedjo Santoso (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
The purpose of this study is to find out empirical evidence about the effect of profitability, dividends, intellectual caputal on the capital structure. The data used in this study is based on companies listed in the Jakarta Islamic Index in the 2019-2022 period. The data analysis technique used multiple regression analysis. Sampling was done using purposive sampling method which then obtained 18 samples of companies. The analytical technique used in this study is the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that profitability has a significant positive effect on capital structure. Dividends have a significant negative effect on the capital structure. Intellectual capital have no effect on the capital structure. Meanwhile, intellectual capital as an intervening variable failed to affect profitability and dividends on the capital structure. Keywords: profitability, dividends, intellectual capital, capital structure.